Community-based health interventions : principles and applications - Guttmacher, Sally; Kelly, Patricia J. [ (Patricia Jane)]; Ruiz-Janecko, Yumary , 1969- (Jossey-Bass, 2010)
"Community Based Health Interventions: Principles and Application is a completely modern approach to worst problems in community health: diabetes, cancer, cardiovascular disease, HIV, asthma, and obesity. Following the trend begun by CDC and other agencies, the book takes a proactive and evidence-based approach reducing risk for individuals and communities. In a step by step approach, the book teaches how to design interventions, how to pick methods, how to assess the interventions? effects, and how to identify and address ethical challenges. The book refers constantly to real-world examples from across the US and also includes international examples of public health issues facing our communities today, and what to do about them.Part I of the book covers the fundamentals of interventions: Intervention rationale, Target population, Community setting, Design, Collaborations and partnerships, Political and organizational influence, Evaluation, Ethics, and Resources.Part II of the book covers types of interventions: formative intervention, informational intervention, social/behavioral, and environmental/policy.Most funding for community-based public health efforts is determined by categorical programs. Therefore, part III of the book is organized by major catagories: Type II Diabetes, Cardiovascular disease, obesity, infectious disease, substance abuse, injury and violence, reproductive and sexual health, cancer, and maternal/child healthThe book?s web site will include links to databases; links to agency and public health resources; intervention tools; instructor guides, slides, assignments; and additional case examples"--Provided by publisher.